Factors Influencing Capital Structure: An Empirical Evaluation of Major Oil and Gas Producing Companies Operating in Ghana - Baidoo, Dennis Amponsah (International Journal of Finance Research, 2022)
A company's choice of capital structure determines how successfully it will operate. This choice heavily depends on the understanding and optimisation of the capital structure factors necessary to increase industry-specific profitability and, consequently, market value. Therefore, the goal of this study is to analyse the factors that determine the capital structure of six significant oil producing companies operating in Ghana, namely: Hess Corporation, Kosmos Energy, Tullow Oil and Ghana National Petroleum Company from 2010 to 2018. In the analysis of panel data for this study, random effect estimation is used. Size, liquidity, tangibility, crude oil price, and profitability are used in conjunction with pertinent literature to describe the factors that determine capital structure, which is proxied by the debt-to-capitalisation ratio (leverage). The findings demonstrated that profitability, firm size, crude oil price, and liquidity are major capital structure factors that have a markedly adverse connection with leverage. The main finding of this study implies that, in accordance with the pecking order theory, consideration of debt may ultimately be the last resort, whereas the management of these major oil and gas companies in Ghana must exercise discretion when considering funding based on debt and rely more on generated profits (retained earnings) and shareholder equity. Appropriate crude oil price hedging instruments are recommended to minimise the impact of commodity price volatility on decisions on capital structure strategies.